Extracorporal shock wave therapy enhances receptor for advanced glycated end-product-dependent flap survival and angiogenesis - Birgin, Emrullah; Gebhardt, Christoffer; Hetjens, Svetlana; Fischer, Sebastian; Rückert, Felix; Reichenberger, Matthias (Annals of plastic surgery, 2018)
Background/ObjectivesLoss of skin flaps due to deteriorated wound healing is a crucial clinical issue. Extracorporal shock wave therapy (ESWT) promotes flap healing by inducing angiogenesis and suppressing inflammation. The receptor for advanced glycation end-products (RAGEs) was identified to play
Gesehen am 06.09.2019